2020
DOI: 10.7759/cureus.7406
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Helicobacter Pylori and Perforated Gastroduodenal Ulcer

Abstract: Background Although the role of Helicobacter pylori (H. pylori) is well known in peptic ulcer disease (PUD) etiology, its role in perforated peptic ulcer (PPU) is not well established. This study aimed to assess the role of H. pylori infection in patients with PPU and to compare it with its prevalence in patients with PUD. Methodology This prospective analytical study was conducted for two years. The study patients were classified into two groups: group I consisted of patients (n = 48) operated for PPU and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Studies by Pescatore et al [7] and Tokunaga et al [8] showed the highest H. pylori prevalence among patients with GDP and ranged from 92% to 100% (n = 119 patients), compared to the other studies that showed a prevalence of infection between 20 and 84.6% (n = 1457) [9][10][11][12][13][14][15][16]. Two of the studies reported the lowest prevalence of H. pylori infection, with 12.5% among a total number of 48 patients and 13.8% among 29 patients with a perforated peptic ulcer, which could be due to the small sample size of both studies [3,17]. 2020) [3] The association between H. pylori and a perforated gastroduodenal ulcer.…”
Section: The Prevalence Of H Pylori Infection Among Patients With Gas...mentioning
confidence: 80%
See 2 more Smart Citations
“…Studies by Pescatore et al [7] and Tokunaga et al [8] showed the highest H. pylori prevalence among patients with GDP and ranged from 92% to 100% (n = 119 patients), compared to the other studies that showed a prevalence of infection between 20 and 84.6% (n = 1457) [9][10][11][12][13][14][15][16]. Two of the studies reported the lowest prevalence of H. pylori infection, with 12.5% among a total number of 48 patients and 13.8% among 29 patients with a perforated peptic ulcer, which could be due to the small sample size of both studies [3,17]. 2020) [3] The association between H. pylori and a perforated gastroduodenal ulcer.…”
Section: The Prevalence Of H Pylori Infection Among Patients With Gas...mentioning
confidence: 80%
“…Two of the studies reported the lowest prevalence of H. pylori infection, with 12.5% among a total number of 48 patients and 13.8% among 29 patients with a perforated peptic ulcer, which could be due to the small sample size of both studies [3,17]. 2020) [3] The association between H. pylori and a perforated gastroduodenal ulcer. 48 12.5% (6) Ha et al ( 2016) [11] The gastrointestinal safety of herbal medicine in patients with osteoarthritis.…”
Section: The Prevalence Of H Pylori Infection Among Patients With Gas...mentioning
confidence: 97%
See 1 more Smart Citation
“…In the present study, 20% of the patients diagnosed with perforated duodenal ulcer mentioned a positive history of NSAIDS intake. Some authors reported a strong evidence of association between NSAIDS intake and duodenal ulcer disease [12,13,14] . It was elucidated that NSAIDs act by inhibiting the COX-II enzyme and thus limiting its gastro-protective effect [15] .…”
Section: Discussionmentioning
confidence: 99%
“…According to a recently published study [15], cigarette smoking was found to increase the risk of infection by Helicobacter pylori, a bacterium known for its major role in ulcerogenesis (70%-80% of ulcers are caused by H. pylori) [16,17]. Indeed, smoking significantly promotes the development and permanence of the ulcer by increasing acid secretion through the increase of the gastric parietal cell mass, by decreasing the secretion of bicarbonate and endogenous prostaglandins, and delaying the ulcer's healing [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%